The Florida Cohort study: methodology, initial findings and lessons learned from a multisite cohort of people living with HIV in Florida. Issue 4 (3rd April 2021) - Ibañez, Gladys E.; Zhou, Zhi; Cook, Christa L.; Slade, Tania A.; Somboonwit, Charurut; Morano, Jaime; Harman, Jeffrey; Bryant, Kendall; Whitehead, Nicole Ennis; Brumback, Babette; Algarin, Angel B.; Spencer, Emma C.; et al.
ABSTRACT: In 2013, Florida had the highest rate of new HIV infections and only 56% of persons living with HIV (PLWH) were virally suppressed. In response, we initiated a new HIV cohort in Florida to better understand issues affecting HIV health outcomes. This manuscript will describe the procedures of the Florida Cohort; summarize information regarding enrollment, follow-up, and findings to date; and discuss challenges and lessons learned during the establishment of a multisite cohort of PLWH. Florida Cohort participants were enrolled from eight clinics and community-based organizations geographically diverse counties across Florida. Data were obtained from participant questionnaires, medical records, and state surveillance data. From 2014–2018, 932 PLWH (44% ≥50 years, 64% male, 55% black, 20% Latinx) were enrolled. At baseline, 83% were retained in care and 75% were virally suppressed. Research findings to date have focused on outcomes such as the HIV care continuum, HIV-related comorbidities, alcohol and drug use, and mHealth interventions interest. Strengths included the diversity of the sample and the linkage of participant surveys with existing surveillance data. However, the study had several challenges during planning and follow-up. The lessons learned from this study can be helpful when initiating a new longitudinal cohort study.